2019
DOI: 10.1080/08870446.2018.1545905
|View full text |Cite|
|
Sign up to set email alerts
|

The role of coping in the relationship between stressful life events and quality of life in persons with cancer

Abstract: Objective: Stressful life events (SLEs) impact the quality of life (QOL) of cancer patients. This study investigated the mediation of the relationship between SLEs and QOL

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 54 publications
4
15
0
1
Order By: Relevance
“…These findings not only suggested the different protective mechanisms for quality of life dimensions but also mirrored previous suggestions as to the variabilities in the effect of a given coping strategy in various situations, especially during the course of cancer ( Reddick et al, 2005 ; Ahlstedt Karlsson et al, 2020 ). In terms of behavioral disengagement, some studies suggested that when aggregated with denial to form disengagement coping, behavioral disengagement could contribute to heightening emotional distress and physical wellbeing, respectively, in higher states of functional impairment ( Merluzzi et al, 2021 ) and lifetime stressful events ( Langford et al, 2017 ; Merluzzi et al, 2019 ). Some other studies also suggested venting to be a function of maladaptive mental processes of pessimism in evoking cancer distress ( David et al, 2006 ), which also showed its lower levels to be functional in terms of arm subscale in the current patients with mastectomy ( n = 153).…”
Section: Discussionmentioning
confidence: 99%
“…These findings not only suggested the different protective mechanisms for quality of life dimensions but also mirrored previous suggestions as to the variabilities in the effect of a given coping strategy in various situations, especially during the course of cancer ( Reddick et al, 2005 ; Ahlstedt Karlsson et al, 2020 ). In terms of behavioral disengagement, some studies suggested that when aggregated with denial to form disengagement coping, behavioral disengagement could contribute to heightening emotional distress and physical wellbeing, respectively, in higher states of functional impairment ( Merluzzi et al, 2021 ) and lifetime stressful events ( Langford et al, 2017 ; Merluzzi et al, 2019 ). Some other studies also suggested venting to be a function of maladaptive mental processes of pessimism in evoking cancer distress ( David et al, 2006 ), which also showed its lower levels to be functional in terms of arm subscale in the current patients with mastectomy ( n = 153).…”
Section: Discussionmentioning
confidence: 99%
“…Disengagement coping has been linked with worse physical symptoms and more emotional distress (i.e., symptoms of clinical depression and anxiety), while the use of engagement coping among women with breast cancer is often associated with less emotional distress across the disease experience (Brunault et al, 2016; De Feudis et al, 2015; Merluzzi et al, 2019; Yu & Sherman, 2015). Still, classification of individual coping responses into higher-order categories of disengagement and engagement coping remains ambiguous, as many research groups have utilized different composites to reflect these constructs in various samples (Compas et al, 2006; Hoyt et al, 2014; Merluzzi et al, 2019; Nahlen Bose et al, 2015).…”
Section: Current Studymentioning
confidence: 99%
“…Disengagement coping has been linked with worse physical symptoms and more emotional distress (i.e., symptoms of clinical depression and anxiety), while the use of engagement coping among women with breast cancer is often associated with less emotional distress across the disease experience (Brunault et al, 2016; De Feudis et al, 2015; Merluzzi et al, 2019; Yu & Sherman, 2015). Still, classification of individual coping responses into higher-order categories of disengagement and engagement coping remains ambiguous, as many research groups have utilized different composites to reflect these constructs in various samples (Compas et al, 2006; Hoyt et al, 2014; Merluzzi et al, 2019; Nahlen Bose et al, 2015). Moreover, research investigating the influence of disengagement and engagement coping on physical and psychological symptoms among women with breast cancer has yielded mixed findings, especially with regard to the directionality and longitudinal nature of these effects (Bonnaud-Antignac et al, 2017; Langford et al, 2017; Merluzzi et al, 2019; A.…”
Section: Current Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, while active coping was positively correlated with caregivers' FACT-G social well-being in both RCTs and with the FACT-G total score in the Advanced Cancer RCT, active coping was not consistently related to other FACT-G subscales. Other studies have also reported mixed findings between QOL and active coping [46][47][48], suggesting that this variable warrants further exploration. We also found strong discriminant validity of the Caregiver FACT-G.…”
Section: Psychometric Properties Of the Caregiver Fact-gmentioning
confidence: 99%